2019
DOI: 10.1080/01587919.2019.1600367
|View full text |Cite
|
Sign up to set email alerts
|

Chronicling engagement: students’ experience of online learning over time

Abstract: While there is ample research into student engagement in online learning, much of this investigates the student experience through surveys administered at a fixed point in time, usually at the exit point of a single unit of study or course. The study described in this paper, by contrast, aimed to understand online student engagement over a whole semester, guided by two overarching questions: What factors impact students' engagement over a semester? What factors account for fluctuation in engagement levels over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 24 publications
7
91
0
2
Order By: Relevance
“…Beyond the role adopted by the instructor, Muir et al (2019) and Norton and Hathaway (2008) found that engagement and perceived quality levels of the online learning experience were the result of students' attitude and commitment. Effective learning occurred when the student was dedicated, prepared, self-motivated, had good support (Muir et al 2019), and provided relevant comments that increased participation and quality interaction (Reeves. and Pedulla 2011;Tang and Lam 2014).…”
Section: The Teaching Presencementioning
confidence: 99%
“…Beyond the role adopted by the instructor, Muir et al (2019) and Norton and Hathaway (2008) found that engagement and perceived quality levels of the online learning experience were the result of students' attitude and commitment. Effective learning occurred when the student was dedicated, prepared, self-motivated, had good support (Muir et al 2019), and provided relevant comments that increased participation and quality interaction (Reeves. and Pedulla 2011;Tang and Lam 2014).…”
Section: The Teaching Presencementioning
confidence: 99%
“…These were the types of learning activities introduced as a replacement or enhancement to conventional face-to-face, the pedagogical approach, and type of communication as synchronous or asynchronous (Means et al, 2009). Failing to address online learning holistically could very well lead to adverse results exemplified in notable student disengagement, lower retention rates, and ineffective overall online learning experience (Muir et al, 2019). Another study on the development of an instructional strategy framework for online learning environments contended that powerful online learning environments needed to contain a combination of: individual needs assessments, student motivational activities, avoidance of information overload, a real-life context, encouragement of social interaction, hands-on activities, and an increased emphasis on student reflection (Johnson and Aragon, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, analysis revealed no statistical difference between residing location and CWA nor between residing location and FPE within these cohorts, despite the known challenges of studying ITE online (Muir et al, 2019). These results suggest that there is potential for these students to remain in these urban, regional and remote areas, fulfilling the needs of their local school communities (McDonnell et al, 2011).…”
Section: Location and Access To Itementioning
confidence: 79%